Factors associated with polypharmacy in residents of an elderly community - Borges Santana, Tamiles Daiane; Giehl Martins Miranda, Camille; Oliveira Damasceno, Rudson; dos Santos, Lucas; Casotti, Cezar Augusto; Fernandes, Marcos Henrique; Oliveira Carneiro, José Ailton (O Mundo da Saúde, 2019)
The practice of polypharmacy in the elderly has often been related to adverse effects, drug interactions, hospitalizations and prolonged hospitalization. In this sense, the objective of the study was to determine the prevalence of polypharmacy in the elderly and to identify the factors associated with this practice using the classification of 3 or more medications. A cross-sectional, population-based and home-based study including 316 elderly (age ≥ 60 years) from a small municipality was conducted. The use of polypharmacy was considered as the concomitant use of 3 or more drugs, and sociodemographic, behavioral and health conditions were collected through a questionnaire. The average age of the elderly was 74.2±9.8 years, with 54.7% being female. The prevalence of elderly who used three or more medications (polypharmacy) was 40.8%; of these, 56.8% reported being hypertensive, 80% diabetic and 65.2% with multimorbidity. In the adjusted analysis, polypharmacy was associated with females (PR = 1.40; 95% CI: 1.08-1.81; p = 0.011), in those aged 70 to 79 years (PR = 1.58; 95% CI: 1.18-2.11; p = 0.002), insufficiently active (PR = 1.41; 95% CI: 1.11-1.78; p = 0.005), hypertensive (PR = 2.37; 95% CI: 1.24-4.52; p = 0.009), diabetic (PR = 1.49; 95% CI: 1.22-1.82; p <0.001) and with multimorbidity (PR = 4.35; IC95 %: 1.20-15.73; p = 0.025). There was a high prevalence of elderly people who use polypharmacy, being associated with females, aged 70 to 79 years old, insufficiently active, hypertensive, diabetic and with multimorbidity. These findings demonstrated that the use of 3 or more medications already exposes the elderly to the risks of polypharmacy.